2020
DOI: 10.1371/journal.pone.0228302
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 upregulation by IFN-α/γ-mediated Stat1 suppresses anti-HBV T cell response

Abstract: Programmed death ligand 1 (PD-L1) has been recently shown to be a major obstacle to antiviral immunity by binding to its receptor programmed death 1 (PD-1) on specific IFN-γ producing T cells in chronic hepatitis B. Currently, IFN-α is widely used to treat hepatitis B virus (HBV) infection, but its antiviral effect vary greatly and the mechanism is not totally clear. We found that IFN-α/γ induced a marked increase of PD-L1 expression in hepatocytes. Signal and activators of transcription (Stat1) was then ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Through STAT1‐related pathways, HBV infection not only induced monocytes to express lower levels of IFN signalling/stimulated genes and higher levels of IL‐10, 32 but also led to the suppression of the anti‐HBV T cell response. 33 , 34 A specific enhancer of STAT1, 2‐NP, rescued IFN signalling in HBV‐infected monocytes, 32 which corroborate our findings that a higher level of STAT1 is found in responders. More studies on the regulatory mechanism of IFN/JAK/STAT signalling may help elucidate the mechanism of persistent HBV infection and the poor response rates to antiviral therapy in CHB patients.…”
Section: Discussionsupporting
confidence: 81%
“…Through STAT1‐related pathways, HBV infection not only induced monocytes to express lower levels of IFN signalling/stimulated genes and higher levels of IL‐10, 32 but also led to the suppression of the anti‐HBV T cell response. 33 , 34 A specific enhancer of STAT1, 2‐NP, rescued IFN signalling in HBV‐infected monocytes, 32 which corroborate our findings that a higher level of STAT1 is found in responders. More studies on the regulatory mechanism of IFN/JAK/STAT signalling may help elucidate the mechanism of persistent HBV infection and the poor response rates to antiviral therapy in CHB patients.…”
Section: Discussionsupporting
confidence: 81%
“…IFN-I suppresses HBV replication when viral load is high and enhances HBV replication when viral load is low via transcriptional and post-transcriptional regulations ( Tian et al, 2011 ). However, some patients suffer from IFN-α treatment resistance by inducing CD24 + CD38 hi B cell and IFN-α/γ-STAT1-PD-L1 axis-mediated downregulating functions of T cells and NK cells ( Fu et al, 2020 ; Liu et al, 2020 ) as well as producing anti-IFN-α Abs ( Porres et al, 1989 ).…”
Section: Cytokines In Hepatitis B Virus Infectionmentioning
confidence: 99%
“…The upregulation of IPS-1, RIG-1, CD80, and HLA-1 indicates that the codelivery complexes would promote antiviral immune responses. In recent years, studies have shown that the expression of PD-L1 plays an important role in the immunosuppression of patients with chronic hepatitis B. Inhibiting the expression of PD-L1 is beneficial to the recovery of immune function in patients with chronic hepatitis B [ 47 , 48 , 49 ]. The cluster of differentiation 47 (CD47) can bind with the signal-regulatory protein alpha (SIRP-α) receptor on immune cells to give a signal of “do not eat me” [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%